2020
DOI: 10.1073/pnas.1913207117
|View full text |Cite
|
Sign up to set email alerts
|

Cotranslational folding allows misfolding-prone proteins to circumvent deep kinetic traps

Abstract: Many large proteins suffer from slow or inefficient folding in vitro. It has long been known that this problem can be alleviated in vivo if proteins start folding cotranslationally. However, the molecular mechanisms underlying this improvement have not been well established. To address this question, we use an all-atom simulation-based algorithm to compute the folding properties of various large protein domains as a function of nascent chain length. We find that for certain proteins, there exists a narrow wind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 63 publications
4
48
0
Order By: Relevance
“…The results of our simulations thus demonstrate the feasibility of a protein folding machine. Some recently published results, including studies of the role of the exit tunnel in nascent chain folding (32)(33)(34)(35)(36) and of direct coupling between ATP hydrolysis and protein refolding by the chaperones of the HSP70 family (37)(38)(39), may be also interpreted as evidence of protein folding in vivo being an active process.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our simulations thus demonstrate the feasibility of a protein folding machine. Some recently published results, including studies of the role of the exit tunnel in nascent chain folding (32)(33)(34)(35)(36) and of direct coupling between ATP hydrolysis and protein refolding by the chaperones of the HSP70 family (37)(38)(39), may be also interpreted as evidence of protein folding in vivo being an active process.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. S10 also shows the energies of native conformations for nascent chain lengths [15][16][17][18][19][20][21][22][23][24][25][26][27]. For proteins in Group 2, we observe that the C-terminal residues for the evolved sequences contribute a greater fraction of the stabilization of the native state than is the case for the unevolved sequences.…”
Section: Two Opposing Strategies For Reaching the Native Statementioning
confidence: 90%
“…The study from our group examined E. coli proteins in particular, finding that conserved rare codons are often located downstream of cotranslational folding intermediates that were identified using a native-centric model of cotranslational protein folding (20). In a subsequent computational study using a more realistic all-atom sequence-based potential, we found that the positions of slowly translating, rare codons could correspond to nascent chains lengths that exhibit stable partly folded states as well as fast folding kinetics (22).…”
Section: Introductionmentioning
confidence: 97%
“…But for larger, more complex proteins, DBFOLD can compute folding pathways at a significantly reduced computational cost relative to direct simulation, which would require unreasonably long simulation times. We quantify this computational speedup for various proteins simulated here and in reference [17] by tallying the total time that was required to run equilibrium simulations to convergence, and to collect sufficient high-temperature unfolding statistics to allow for extrapolation prior to use of DBFOLD (Fig. 7, rightmost column).…”
Section: Determining Validity Of Conditions I and Iimentioning
confidence: 99%
“…Such intermediates can be detrimental in vivo, where they may be degraded, form toxic oligomers, or aggregate, potentially leading to loss of fitness and/or disease [1][2][3][4][5][6][7]. Organisms deploy various cellular mechanisms to mitigate protein misfolding including chaperones [4,[8][9][10] and co-translational folding on the ribosome [5,[11][12][13][14][15][16][17], which may be enhanced by slowly translating codons located at nascent chain lengths that show optimal folding properties [15][16][17]. Despite the fact that non-native folding intermediates exert widespread and significant consequences, we have yet to develop a detailed atomstic understanding of how they slow folding, and how cellular mechanisms reduce their formation and detrimental effects.…”
Section: Introductionmentioning
confidence: 99%